Modelo de avaliação para apoiar a preparação de um sistema produtivo para a implantação do sistema de produção enxuta - Gehres, Fernando Fischer (Universidade do Vale do Rio dos Sinos, 2017)
Brazilian economy recession in the last two years led to a growing competition in the industry. Companies based their survival on productivity and efficiency enhancement. One possible alternative is Lean Manufacturing implementation, based on Toyota Production System. Nevertheless, literature reports low success rates on Lean Manufacturing implementation (between 10 and 20%). This research investigates the reasons for such a low success rate thought a case study on two metal industries. In order to identify the failure root causes, Current Reality Trees, derived from Theory of Constraints Thinking Process, were used. Based on the root causes, a Self-assessment Model was proposed to grade company situation before Lean Manufacturing implementation process starts. This way, deficiencies can be timely identified and actions taken, incresing success opportunity.
Keywords: Sistema de produção enxuta; Produtividade; Taxa de sucesso; Causas-raízes; Árvore da realidade atual; Modelo de diagnóstico; Lean manufacturing; Productivity; Success rate; Root causes; Current reality tree; Self-assessment model; ACCNPQ::Engenharias::Engenharia de Produção